Enterprise Architecture: Digital Transformation of BPRCCo SMEs Using TOGAF 10 - Wafiyah, Afifah Hasna; Mulyana, Rahmat; Fajrillah, Asti Amalia Nur (LPPM STIKOM Tunas Bangsa, 2024)
Digital Transformation (DT) is a challenge for banks in Indonesia. Previous research has shown that IT strategy and architecture is one of the key governance mechanisms that play an important role in the success of DT in the Indonesian banking industry. However, this research has not been proven for the small-scale banking sector, in particular BPRCCo as an SME bank. Enterprise architecture (EA) is a method that can be used to align business and IT strategy. This research uses the Design Science Research (DSR) method, which includes problem explication, requirement specification, design and development, demonstration, and evaluation. Data was gathered through semi-structured interviews, validated using document triangulation, and analyzed using the TOGAF 10 framework, from the preliminary phase through technology architecture, producing blueprint for BPRCCo roadmap 2024-2026. This research contributes to the knowledge base of EA in DT for SMEs and guidance for BPRCCo and similar organizations in implementing prioritized artifacts for successful DT.